PM10 as Predictor of Ventilation Efficiency of Houses in Relation to Health Effect (Medical Journal of Indonesia, 2005)
Concerns for the high concentration of particulates in the ambient air of Jakarta had been associated with respiratory health effects. Accordingly, the high concentration of indoor air particulate in homes was also recognized as a potential health hazard to the household. This paper was based on findings in a cross-sectional study in homes of a village, Jakarta done for a dissertation of a doctoral degree in Public Health. In relation to health aspect, ventilation effectiveness was more predicted by the variation of indoor particulates concentrations (as PM10) than the physical characteristic of the houses. Besides, respiratory symptoms rates among children under-five were positively associated to PM10 concentrations. Except for the house dampness factor, no physical features of the houses such as sizes of windows, rooms, and the like, contributed to the variability of health of the occupants. This research suggested that PM10 concentration was a better indicator for a healthy house than the physical characteristics of the house. As such, the most sensitive and specific level of PM10 concentration to predict the development of respiratory symptoms was 70 µg/m3. This cut-off concentration of PM10 agreed with the guideline value set on the level of 70 µg/m3 for the thoracic particles by the World Health Organization. (Med J Indones 2005; 14: 237-41)